Effects of quenching process on the optical properties of thin film polymers - Jumpar-Ngern, Jitrin; Sompong, Khanisorn; Wasapinyokul, Kamol (My University, 2019)
Polymer is a group of materials applied in several thin film electronic devices. A typical fabrication process of the material consists of coating it as a film onto a substrate by a wet process, followed by the baking and annealing the film to change its molecular structures, and hence its properties. In this study, we reported the effect of the quenching process, or the cooling down process after baking, on the optical transmittance of the film. Thin films of poly(methyl methacrylate), or PMMA, was coated on a substrate and then baked at different temperatures followed by either a quick or slow cool-down quenching process; before they were checked for their optical transmittances. The results showed that the film baked at a temperature slightly higher than the glass transition temperature of the polymer, followed by a slow cool-down quenching process would provide the transmittance apparently lower than those of the films baking and quenching at other conditions. We believe that this was because when the polymer was baked above such temperature, the polymer was in its glassy state. When it was slowly cooled down, the molecules had time to form crystalline structure, hence a lower optical transmittance. The result from this study indicated that the quenching process can be used to control the properties of a polymer film and hence should be carefully practiced.
Keywords: Annealing; Baking; Optical transmittance; Poly(methyl methacrylate); Polymer; Quenching process